Flexible Fixation Technique for Lisfranc Injuries. (November 2019) - Delman, Connor; Patel, Midhat; Campbell, Mark; Kreulen, Christopher; Giza, Eric
Injuries to the Lisfranc complex range from purely ligamentous disruptions to fracture-dislocations of the tarsometatarsal joint. Treatment options include closed/open reduction with percutaneous pinning, open reduction and internal fixation (ORIF), and primary arthrodesis. We present a ligament reinforcement technique utilizing a flexible fixation device for the treatment of ligamentous Lisfranc injuries. Level of Evidence: Level V, expert opinion.